2021
DOI: 10.3390/app11136160
|View full text |Cite
|
Sign up to set email alerts
|

BIM Environment Based Virtual Desktop Infrastructure (VDI) Resource Optimization System for Small to Medium-Sized Architectural Design Firms

Abstract: The recent fourth industrial revolution and the era of post-COVID-19 have ushered in a series of technologies including a 5G network and online systems, such as cloud computing technology. In other industries, extensive studies on cloud platforms utilizing such technologies were conducted. Although the cloud environment has taken on greater importance in the construction sector as well, it was used only for servers, failing to fully reflect the characteristics of the cloud system. In particular, compared to la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…As such, the use of Cloud ERP to achieve innovation has received growing attention in both academia and practice in contemporary societies. Specifically, a group of four different types of cloud computing services, including Software as a Service (SaaS), Platform as a Service (PaaS), Infrastructure as a Service (IaaS) and Desktop as a Service (DaaS), can offer several strategic solutions (Lee et al, 2021;Magaña et al, 2019;Jarraya and Elloumi, 2022). Therefore, enterprises can utilise such cloud service models to efficiently generate a digital workspace.…”
Section: Theoretical Implications and Future Research Avenuesmentioning
confidence: 99%
“…As such, the use of Cloud ERP to achieve innovation has received growing attention in both academia and practice in contemporary societies. Specifically, a group of four different types of cloud computing services, including Software as a Service (SaaS), Platform as a Service (PaaS), Infrastructure as a Service (IaaS) and Desktop as a Service (DaaS), can offer several strategic solutions (Lee et al, 2021;Magaña et al, 2019;Jarraya and Elloumi, 2022). Therefore, enterprises can utilise such cloud service models to efficiently generate a digital workspace.…”
Section: Theoretical Implications and Future Research Avenuesmentioning
confidence: 99%
“…Earlier literature omits aspects such as potential VDI software-update issues, though more recent studies address these (Lee et al, 2021). Most testing in the literature was done after system deployment, but none was done during VDI development to inform final platform set-up.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Accordingly, the last few years have been characterised by many HBIM projects and methods capable of managing the paradigm of the complexity of historical buildings and archaeological sites in heterogeneous ways, extending the concept of BIM to that of heritage [44][45][46][47][48][49][50][51][52][53][54][55][56][57]. HBIM projects have been improved by integrating various technologies such as 3D survey, laser scanning, digital photogrammetry (terrestrial and UAV) and AMT [58][59][60][61][62]. In this context, it was found that the understanding and interpretation of each artefact surveyed from a typological point of view is fundamental in the model generation phase.…”
Section: State-of-the-artmentioning
confidence: 99%